The Flowering Characters Variation Among Floral Variants and Landraces Along Geographical Gradients in Gunung Sewu - Yeni Widyana Nurcahyani Cahyaningrum; Sapto Indrioko; Eny Faridah; Atus Syahbudin (Jurnal Ilmu Kehutanan)
Sandalwood was origin to the south-eastern islands of Indonesia, but is recently occured as new land-races in Gunung Sewu, Java island. All of land-races consisted of three floral variants (MK, refers to “merah kecil”; MB, “merah besar”; and KB, “kuning besar”, respectively). This research aimed to determine flowering of these variants among three of land-races which were representing geographical zone in Gunung Sewu: Nglanggeran, Blebera, and Petir. Observation on phenology, sexual organs maturity, floral structure, and display was conducted in 2015. Floral structures varied among variants. MB and KB dominated by red and maroon colors, possessed bigger perigonium, longer sexual organs but with shorter longevity, and similar/lower position of stylus to stamens. MK dominated by yellow to orange colors, smaller, similar/higher position of stylus, and longer longevity. Floral display varied among land-races but were similar among variants. Petir, with biggest population size, produced the most abundant flowers and flowering trees at all variants. Sandalwood flowered twice a year in all of land-races and variants, however, the onset and duration varied. KB flowered earliest while MB was the latest. MK possessed longest flowering period. Flowering varied among land-races due to the altitude, soils, and climatic differences. Lower altitude, drier, and warmer sites flowered earlier and shorter. Mass abortion and sequential replacement, resulting in the alteration on flowering frequency, occured due to the extreme temperature increment. Conservation strategy should be arranged based on genetic differentiation, flowering differences, and crossing abilities among variants. Differences of landscapes, which may contribute to the differences of environmental conditions and flowering processes, should also be considered.